1991
DOI: 10.1172/jci115287
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute systemic hyperinsulinemia on forearm muscle proteolysis in healthy man.

Abstract: To investigate the mechanism(s) of insulin-induced suppression of plasma amino acid concentration and release, we studied forearm as well as whole-body leucine and phenylalanine uptake and release during a peripheral insulin infusion in postabsorptive normal subjects using isotope-dilution methods. Before insulin, leucine and phenylalanine release exceeded uptake (P < 0.01 and P < 0.07, respectively). A net output of a-ketoisocaproate (KIC) was also observed. During insulin, arterial plasma leucine, KIC and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 32 publications
7
48
1
Order By: Relevance
“…The relatively lower mitochondrial content of aging muscle (32) and the decrease in mitochondrial protein synthesis that occurs with aging (16) render support to the above explanation for the discrepancy between studies performed in young and older animals. Lack of demonstrable effect of insulin on mixed muscle protein synthesis in humans is based on studies performed in mature adults (8,(11)(12)(13)(14). The differences between these human studies and studies in growing animals must therefore be cautiously interpreted, and the discrepancies could be resolved by studies based on measurements of synthesis rates of individual muscle proteins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively lower mitochondrial content of aging muscle (32) and the decrease in mitochondrial protein synthesis that occurs with aging (16) render support to the above explanation for the discrepancy between studies performed in young and older animals. Lack of demonstrable effect of insulin on mixed muscle protein synthesis in humans is based on studies performed in mature adults (8,(11)(12)(13)(14). The differences between these human studies and studies in growing animals must therefore be cautiously interpreted, and the discrepancies could be resolved by studies based on measurements of synthesis rates of individual muscle proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all human studies, with one exception (11), have reported that insulin infusion given either systemically (8,12,13) or regionally (14) does not stimulate muscle protein synthesis. Supraphysiological insulin administration, however, has been shown to stimulate muscle protein synthesis based on an arteriovenous model (15).…”
mentioning
confidence: 99%
“…The mode of insulin infusion appears to be a major factor in determining whether or not muscle protein synthesis will be stimulated. For example, systemic insulin infusions decrease blood amino acid concentrations (10,11,24,27,35) unless amino acids are replaced by an exogenous infusion (15,17,24,25,27). On the other hand, local insulin infusion into the leg exposes the muscle tissue to relatively high insulin levels while avoiding a major reduction in blood amino acid concentrations (2, 23).…”
mentioning
confidence: 99%
“…insulin administration is followed by a dosedependent reduction in circulating plasma amino acid levels, with the branched chain amino acids being most sensitive to the increase in circulating insulin levels (59). This insulin-induced hypoaminoacidemia is a reflection of increased amino acid uptake from the plasma in combination with the proposed inhibitory action of increasing insulin levels on endogenous proteolysis (50,60). It has been suggested that the proposed positive effect of exogenous insulin administration on muscle protein synthesis is mediated by insulin-induced increase in blood flow and subsequent greater amino acid delivery to the muscle.…”
Section: Discussionmentioning
confidence: 98%
“…In model 1, study arms were excluded in which the insulin administration was combined with amino acid co-interventions that raised plasma amino acid above basal levels and did not have a comparator group to correct for the increase in plasma amino acids Model 2 additionally excluded study arms in which amino acid levels were allowed to drop below basal levels (41,49,50,51,52,53,54,55). This criterion excluded an additional ten study arms compared with model 1, none of which reported an effect on muscle protein synthesis.…”
Section: Data Synthesismentioning
confidence: 99%